2021
DOI: 10.1007/s40747-021-00386-x
|View full text |Cite
|
Sign up to set email alerts
|

A new mathematical model for determining optimal workforce planning of pilots in an airline company

Abstract: This study aims to model a workforce-planning problem of pilot roles which include captain and first officer in an airline company and to make an efficient plan having maximal utilization of minimum workforce requirements. To tackle this problem, a mixed integer programming based a new mathematical model is proposed. The model considers different conditions such as employing pilots with different skill types, resignations, retirements, holidays of pilots, transitions between different skills regarding needs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Linear programming [22] Mixed integer linear programming [4], [5], [12] Integer programming [31] Goal programming [9], [11] Genetic algorithm [9], [23] System dynamics [8], [23] Discrete-Event Simulation Model [11] Stochastic programming [30] Robust optimization [11] Optimization is often the preferred method for solving the workforce planning issues in cleaning service operations. This is because it can help minimize costs and increase efficiency while ensuring all cleaning tasks are completed on time.…”
Section: Methods Authormentioning
confidence: 99%
See 3 more Smart Citations
“…Linear programming [22] Mixed integer linear programming [4], [5], [12] Integer programming [31] Goal programming [9], [11] Genetic algorithm [9], [23] System dynamics [8], [23] Discrete-Event Simulation Model [11] Stochastic programming [30] Robust optimization [11] Optimization is often the preferred method for solving the workforce planning issues in cleaning service operations. This is because it can help minimize costs and increase efficiency while ensuring all cleaning tasks are completed on time.…”
Section: Methods Authormentioning
confidence: 99%
“…For instance, MILP is employed in addressing the workforce planning problems that involve task duration as a continuous variable in the constraints, as highlighted by [4,5]. In another study conducted by study [12] demonstrated the effectiveness of MILP in addressing the workforce planning problems that involve pilot holidays as a continuous variable in the constraints. The study showed that MILP was able to produce a highly effective performance in this regard.…”
Section: Methods Authormentioning
confidence: 99%
See 2 more Smart Citations
“…It simulates the behavior of grey wolves in nature. Since 2014, GWO have been employed successfully in variety of real-world optimization problems such as scheduling problems [Abed-alguni and Alawad, 2021], text mining [Chantar et al, 2019], aerial vehicles path planning [Qu et al, 2020] and others [Erdogan et al, 2021, Deveci and Çetin Demirel, 2018, Çetin Demirel and Deveci, 2017, Akyurt et al, 2021, Sharma et al, 2020. GWO algorithm has several advantages such as it is simple, easy to use, has fewer parameters that need to be tuned, and has an excellent switching mechanism between exploration and exploitation processes while searching for an optimal solution .…”
Section: Introductionmentioning
confidence: 99%